<meta http-equiv="refresh" content="1; url=/nojavascript/">
Dismiss
Skip Navigation
You are reading an older version of this FlexBook® textbook: CK-12 Trigonometry - Second Edition Go to the latest version.

Chapter 3: Trigonometric Identities and Equations

Difficulty Level: At Grade Created by: CK-12

Chapter Outline

Chapter Summary

Chapter Summary

Here are the identities studied in this chapter:

Quotient & Reciprocal Identities

\tan \theta &= \frac{\sin \theta}{\cos \theta} \qquad \cot \theta = \frac{\cos \theta}{\sin \theta}\\\csc \theta &= \frac{1}{\sin \theta} \ \sec \theta = \frac{1}{\cos \theta} \ \cot \theta = \frac{1}{\tan \theta}

Pythagorean Identities

\sin^2 \theta + \cos^2 \theta = 1 && 1 + \cot^2 \theta = \csc^2 \theta && \tan^2 \theta + 1 = \sec^2 \theta

Even & Odd Identities

\sin (-x) &= -\sin x && \cos (-x) = \cos x && \tan (-x) = -\tan x\\\csc (-x) & = -\csc x && \sec (-x) = \sec x && \cot (-x) = -\cot x

Co-Function Identities

& \sin \left ( \frac{\pi}{2} - \theta \right ) = \cos \theta && \cos \left ( \frac{\pi}{2} - \theta \right ) = \sin \theta && \tan \left ( \frac{\pi}{2} - \theta \right ) = \cot \theta\\& \csc \left ( \frac{\pi}{2} - \theta \right )= \sec \theta && \sec \left ( \frac{\pi}{2} - \theta \right ) = \csc \theta && \cot \left ( \frac{\pi}{2} - \theta \right ) = \tan \theta

Sum and Difference Identities

\cos(\alpha + \beta) & = \cos \alpha \cos \beta - \sin \alpha \sin \beta && \cos(\alpha - \beta) = \cos \alpha \cos \beta + \sin \alpha \sin \beta \\\sin(\alpha + \beta) & = \sin \alpha \cos \beta + \cos \alpha \sin \beta && \sin(\alpha - \beta) = \sin \alpha \cos \beta - \cos \alpha \sin \beta \\\tan (\alpha + \beta) & = \frac{\tan \alpha + \tan \beta}{1 - \tan \alpha \tan \beta} && \tan(\alpha - \beta) = \frac{\tan \alpha - \tan \beta}{1 + \tan \alpha \tan \beta}

Double Angle Identities

\cos(2 \alpha) & = \cos^2 \alpha - \sin^2 \alpha = 2 \cos^2 \alpha - 1 = 1 - 2 \sin^2 \alpha \\\sin(2 \alpha) & = 2 \sin \alpha \cos \beta \\\tan (2 \alpha) & = \frac{2 \tan \alpha}{1 - \tan^2 \alpha}

Half Angle Identities

\cos \frac{\alpha}{2} = \pm \sqrt{\frac{1 + \cos \alpha}{2}} && \sin \frac{\alpha}{2} = \pm \sqrt{\frac{1 - \cos \alpha}{2}} && \tan \frac{\alpha }{2} =  \frac{1 - \cos \alpha}{\sin \alpha} = \frac{\sin \alpha}{1 + \cos \alpha}

Product to Sum & Sum to Product Identities

\sin a + \sin b & = 2 \sin \frac{a+b}{2} \cos \frac{a-b}{2} && \sin a \sin b = \frac{1}{2} [\cos (a-b) - \cos (a+b)] \\\sin a - \sin b& = 2 \sin \frac{a-b}{2} \cos \frac{a+b}{2} && \cos a \cos b = \frac{1}{2} [\cos (a-b) + \cos (a+b)] \\\cos a + \cos b & = 2 \cos \frac{a+b}{2} \cos \frac{a-b}{2} && \sin a \cos b = \frac{1}{2} [\sin (a+b) + \sin (a-b)] \\\cos a - \cos b & = 2 - 2 \sin \frac{a+b}{2} \sin \frac{a-b}{2} && \cos a \sin b = \frac{1}{2} [\sin (a+b) - \sin (a-b)]

Linear Combination Formula

A \cos x + B \sin x = C \cos (x - D), where C = \sqrt{A^2 + B^2}, \cos D = \frac{A}{C} and \sin D = \frac{B}{C}

Review Questions

  1. Find the sine, cosine, and tangent of an angle with terminal side on (-8, 15).
  2. If \sin a = \frac{\sqrt{5}}{3} and \tan a < 0, find \sec a.
  3. Simplify: \frac{\cos^4 x - \sin^4 x}{\cos^2 x - \sin^2 x}.
  4. Verify the identity: \frac{1 + \sin x}{\cos x \sin x} = \sec x (\csc x + 1)

For problems 5-8, find all the solutions in the interval [0, 2\pi).

  1. \sec \left (x + \frac{\pi}{2} \right ) + 2 = 0
  2. 8 \sin \left (\frac{x}{2} \right ) - 8 = 0
  3. 2 \sin^2 x + \sin 2x =0
  4. 3 \tan^2 2x = 1
  5. Solve the trigonometric equation 1 - \sin x = \sqrt{3} \sin x over the interval [0, \pi].
  6. Solve the trigonometric equation 2 \cos 3x - 1 = 0 over the interval [0, 2\pi].
  7. Solve the trigonometric equation 2 \sec^2 x - \tan^4 x = 3 for all real values of x.

Find the exact value of:

  1. \cos 157.5^\circ
  2. \sin \frac{13 \pi}{12}
  3. Write as a product: 4(\cos 5x + \cos 9x)
  4. Simplify: \cos(x - y) \cos y - \sin(x - y) \sin y
  5. Simplify: \sin \left (\frac{4 \pi}{3} - x \right ) + \cos \left (x + \frac{5 \pi}{6} \right )
  6. Derive a formula for \sin 6x.
  7. If you solve \cos 2x = 2 \cos^2x - 1 for \cos^2 x, you would get \cos^2 x = \frac{1}{2} (\cos 2x + 1). This new formula is used to reduce powers of cosine by substituting in the right part of the equation for \cos^2 x. Try writing \cos^4 x in terms of the first power of cosine.
  8. If you solve \cos 2x = 1 - 2 \sin^2 x for \sin^2x, you would get \sin^2 x = \frac{1}{2} (1 - \cos 2x). Similar to the new formula above, this one is used to reduce powers of sine. Try writing \sin^4x in terms of the first power of cosine.
  9. Rewrite in terms of the first power of cosine:
    1. \sin^2x \cos^2 2x
    2. \tan^4 2x

Review Answers

  1. If the terminal side is on (-8,15), then the hypotenuse of this triangle would be 17 (by the Pythagorean Theorem, c = \sqrt{(-8)^2 + 15^2}). Therefore, \sin x = \frac{15}{17}, \cos x = - \frac{8}{17}, and \tan x = - \frac{15}{8}.
  2. If \sin a = \frac{\sqrt{5}}{3} and \tan a < 0, then a is in Quadrant II. Therefore \sec a is negative. To find the third side, we need to do the Pythagorean Theorem. \left (\sqrt{5} \right )^2 + b^2 & = 3^2 \\5 + b^2 & = 9\\b^2 & = 4 \\b & = 2 So \sec a = -\frac{3}{2}.
  3. Factor top, cancel like terms, and use the Pythagorean Theorem Identity. Note that this simplification doesn't hold true for values of x that are \frac{\pi}{4} + \frac{n\pi}{2}, where n is a positive integer,, since the original expression is undefined for these values of x. & \qquad \qquad \frac{\cos^4 x - \sin^4 x}{\cos^2 x - \sin^2 x} \\& \frac{(\cos^2 x + \sin^2 x)(\cos^2 x - \sin^2 x)}{\cos^2 x - \sin^2 x} \\& \qquad \qquad \frac{\cos^2 x + \sin^2 x}{1} \\& \qquad \qquad \frac{1}{1} \\& \qquad \qquad 1
  4. Change secant and cosecant into terms of sine and cosine, then find a common denominator. \frac{1 + \sin x}{\cos x \sin x} & = \sec x (\csc x + 1) \\& = \frac{1}{\cos x} \left (\frac{1}{\sin x} + 1 \right ) \\& = \frac{1}{\cos x} \left (\frac{1 + \sin x}{\sin x} \right ) \\& = \frac{1 + \sin x}{\cos x \sin x}
  5. \sec \left (x + \frac{\pi}{2} \right ) + 2 & = 0 \\\sec \left (x + \frac{\pi}{2} \right ) & = -2 \\\cos \left (x + \frac{\pi}{2} \right ) & = - \frac{1}{2} \\x + \frac{\pi}{2} & = \frac{2 \pi}{3}, \frac{4 \pi}{3} \\x & = \frac{2 \pi}{3} - \frac{\pi}{2}, \frac{4 \pi}{3} - \frac{\pi}{2} \\x & = \frac{\pi}{6}, \frac{5 \pi}{6}
  6. 8 \sin \left (\frac{x}{2} \right ) - 8 & = 0 \\8 \sin \frac{x}{2} & = 8 \\\sin \frac{x}{2} & = 1 \\\frac{x}{2} & = \frac{x}{2} \\x & = \pi
  7. & \qquad \ \  2 \sin^2 x + \sin 2x = 0 \\& 2 \sin^2 x + 2 \sin x \cos x = 0 \\& \ 2 \sin x (\sin x + \cos x) = 0 \\& \ \text{So},\ 2 \sin x = 0 \qquad \quad \text{or}\qquad \quad  \sin x + \cos x = 0 \\& \qquad 2 \sin x = 0 \qquad \qquad \qquad \quad \sin x + \cos x = 0 \\& \qquad \ \ \sin x = 0 \qquad \qquad \qquad \qquad \qquad \ \sin x = - \cos x \\& \qquad \qquad \ x = 0, \pi \qquad \qquad \qquad \qquad \qquad \quad  x = \frac{3\pi}{4}, \frac{7 \pi}{4}
  8. 3\tan^2 2x & = 1 \\\tan^2 2x & = \frac{1}{3} \\\tan 2x & = \pm\frac{\sqrt{3}}{3} \\2x & = \frac{\pi}{6}, \frac{5 \pi}{6}, \frac{7 \pi}{6}, \frac{11 \pi}{6}, \frac{13 \pi}{6}, \frac{17 \pi}{6}, \frac{19 \pi}{6}, \frac{23 \pi}{6} \\x & = \frac{\pi}{12}, \frac{5 \pi}{12}, \frac{7 \pi}{12}, \frac{11 \pi}{12}, \frac{13 \pi}{12}, \frac{17 \pi}{12}, \frac{19 \pi}{12}, \frac{23 \pi}{12}
  9. 1 - \sin x & = \sqrt{3} \sin x \\1 & = \sin x + \sqrt{3} \sin x \\1 & = \sin x \left (1 + \sqrt{3} \right ) \\\frac{1}{1 + \sqrt{3}} & = \sin x \sin^{-1} \left (\frac{1}{1 + \sqrt{3}} \right ) = x or x = .3747 radians and x = 2.7669 radians
  10. Because this is \cos 3x, you will need to divide by 3 at the very end to get the final answer. This is why we went beyond the limit of 2\pi when finding 3x. 2 \cos 3x - 1 & = 0 \\2 \cos 3x & = 1 \\\cos 3x & = \frac{1}{2} \\3x & = \cos^{-1} \left (\frac{1}{2} \right ) = \frac{\pi}{3},\frac{5 \pi}{3}, \frac{7 \pi}{3}, \frac{11 \pi}{3}, \frac{13 \pi}{3}, \frac{17 \pi}{3} \\x & = \frac{\pi}{9},\frac{5 \pi}{9}, \frac{7 \pi}{9}, \frac{11 \pi}{9}, \frac{13 \pi}{9}, \frac{17 \pi}{9}
  11. Rewrite the equation in terms of tan by using the Pythagorean identity, 1 + \tan^2 \theta = \sec^2 \theta. 2 \sec^2 x - \tan^4 x & = 3 \\2 (1 + \tan^2 x) - \tan^4 x & = 3 \\2 + 2 \tan^2 x - \tan^4 x & = 3 \\\tan^4 x - 2 \tan^2 x + 1 & = 0 \\(\tan^2 x - 1)(\tan^2 x - 1) & = 0 Because these factors are the same, we only need to solve one for x. \tan^2 x - 1 & = 0 \\\tan^2 x & = 1 \\\tan x & = \pm 1 \\x & = \frac{\pi}{4} + \pi k \ \text{and}\ \frac{3 \pi}{4} + \pi k Where k is any integer.
  12. Use the half angle formula with 315^\circ. \cos 157.5^\circ & = \cos \frac{315^\circ}{2} \\& = - \sqrt{\frac{1 + \cos 315^\circ}{2}} \\& = - \sqrt{\frac{1 + \frac{\sqrt{2}}{2}}{2}} \\& = - \sqrt{\frac{2 + \sqrt{2}}{4}} \\& = - \frac{\sqrt{2 + \sqrt{2}}}{2}
  13. Use the sine sum formula. \sin \frac{13 \pi}{12} & = \sin \left (\frac{10 \pi}{12} + \frac{3 \pi}{12} \right ) \\& = \sin \left (\frac{5 \pi}{6} + \frac{\pi}{4} \right ) \\& = \sin \frac{5 \pi}{6} \cos \frac{\pi}{4} + \cos \frac{5 \pi}{6} \sin \frac{\pi}{4} \\& = \frac{1}{2} \cdot \frac{\sqrt{2}}{2} + (-\frac{\sqrt{3}}{2}) \cdot \frac{\sqrt{2}}{2} \\& = \frac{\sqrt{2} - \sqrt{6}}{4}
  14. 4 (\cos 5x + \cos 9x) & = 4 \left [2 \cos \left (\frac{5x + 9x}{2} \right ) \cos \left (\frac{5x - 9x}{2} \right ) \right ] \\& = 8 \cos 7x \cos (-2x) \\& = 8 \cos 7x \cos 2x
  15. & \qquad \qquad \qquad \cos(x - y) \cos y - \sin(x - y) \sin y \\ & \cos y (\cos x \cos y + \sin x \sin y) - \sin y\ (\sin x \cos y - \cos x \sin y) \\& \cos x \cos^2 y + \sin x \sin y \cos y - \sin x \sin y \cos y + \cos x \sin^2 y \\ & \qquad \qquad \qquad \quad \cos x \cos^2y + \cos x \sin^2 y \\ & \qquad \qquad \qquad \quad \cos x (\cos^2y + \sin^2 y) \\ & \qquad \qquad \qquad \qquad \qquad \cos x
  16. Use the sine and cosine sum formulas. & \qquad \qquad \qquad \sin \left (\frac{4 \pi}{3} - x \right ) + \cos \left (x + \frac{5 \pi}{6} \right ) \\& \sin \frac{4 \pi}{3} \cos x - \cos \frac{4 \pi}{3} \sin x + \cos x \cos \frac{5 \pi}{6} - \sin x \sin \frac{5 \pi}{6} \\& \qquad - \frac{\sqrt{3}}{2} \cos x + \frac{1}{2} \sin x - \frac{\sqrt{3}}{2} \cos x - \frac{1}{2} \sin x \\& \qquad \qquad \qquad \qquad \qquad - \sqrt{3} \cos x
  17. Use the sine sum formula as well as the double angle formula.  \sin 6x & = \sin (4x + 2x) \\& = \sin  4x \cos 2x + \cos 4x \sin  2x \\& = \sin(2x + 2x) \cos 2x + \cos (2x + 2x) \sin  2x \\& = \cos 2x\ (\sin  2x \cos 2x + \cos 2x \sin  2x) + \sin 2x(\cos 2x \cos 2x - \sin  2x\ \sin  2x) \\& = 2 \sin  2x \cos^2 2x + \sin  2x \cos^2 2x - \sin^3 2x \\& = 3 \sin  2x\ \cos^2 2x - \sin^3 2x \\& = \sin  2x(3 \cos^2 2x - \sin^2 2x) \\& = 2 \sin  x \cos x [3(\cos^2 x - \sin^2 x)^2 - (2 \sin  x \cos x)^2 \\& = 2 \sin  x \cos x [3(\cos^4 x - 2 \sin^2 x \cos^2 x + \sin^4 x) - 4\ \sin^2 x \cos^2 x] \\& = 2 \sin  x \cos x [3 \cos^4 x - 6 \sin^2 x \cos^2 x + 3 \sin^4 x - 4\ \sin^2 x \cos^2 x] \\& = 2 \sin  x \cos x [3 \cos^4 x + 3 \sin^4 x - 10 \sin^2 x \cos^2 x] \\& = 6 \sin  x \cos^5 x + 6 \sin^5 x \cos x - 20 \sin^3x \cos^3x
  18. Using our new formula, \cos^4 x = \left [\frac{1}{2}(\cos 2x + 1) \right ]^2 Now, our final answer needs to be in the first power of cosine, so we need to find a formula for \cos^2 2x. For this, we substitute 2x everywhere there is an x and the formula translates to \cos^2 2x = \frac{1}{2}(\cos 4x + 1). Now we can write \cos^4 x in terms of the first power of cosine as follows. \cos^4 x&=[\frac{1}{2}(\cos 2x+1)]^2 \\&=\frac{1}{4}(\cos^2 2x+2\cos 2x+1) \\&=\frac{1}{4}(\frac{1}{2}(\cos 4x+1)+2\cos 2x+1) \\&=\frac{1}{8}\cos 4x+\frac{1}{8}+\frac{1}{2}\cos 2x+\frac{1}{4} \\&=\frac{1}{8}\cos 4x+\frac{1}{2}\cos 2x+\frac{3}{8}
  19. Using our new formula, \sin^4 x = \left [\frac{1}{2}(1 - \cos 2x) \right ]^2 Now, our final answer needs to be in the first power of cosine, so we need to find a formula for \cos^2 2x. For this, we substitute 2x everywhere there is an x and the formula translates to \cos^2 2x = \frac{1}{2}(\cos 4x + 1). Now we can write \sin^4 x in terms of the first power of cosine as follows. \sin^4 x&=[\frac{1}{2}(1-\cos 2x)]^2 \\&=\frac{1}{4}(1-2\cos 2x + \cos^2 2x) \\&=\frac{1}{4}(1-2\cos 2x + \frac{1}{2}(\cos 4x + 1)) \\&=\frac{1}{4} - \frac{1}{2}\cos 2x + \frac{1}{8}\cos 4x + \frac{1}{8} \\&=\frac{1}{8}\cos 4x - \frac{1}{2}\cos 2x + \frac{3}{8}
  20. (a) First, we use both of our new formulas, then simplify: \sin^2 x \cos^2 2x & = \frac{1}{2}(1 - \cos 2x) \frac{1}{2}(\cos 4x + 1) \\& = \left (\frac{1}{2} - \frac{1}{2} \cos 2x \right ) \left (\frac{1}{2} \cos 4x + \frac{1}{2} \right ) \\& = \frac{1}{4} \cos 4x + \frac{1}{4} - \frac{1}{4} \cos 2x \cos 4x - \frac{1}{4} \cos 2x \\& = \frac{1}{4} (1 - \cos 2x + \cos 4x - \cos 2x \cos 4x) (b) For tangent, we use the identity \tan x = \frac{\sin x}{\cos x} and then substitute in our new formulas. \tan^4 2x = \frac{\sin^4 2x}{\cos^4 2x} \rightarrow Now, use the formulas we derived in #18 and #19.
  21. \tan^4 2x &= \frac{\sin^4 2x}{\cos^4 2x} \\&=\frac{\frac{1}{8}\cos 8x - \frac{1}{2}\cos 4x + \frac{3}{8}}{\frac{1}{8}\cos 8x+\frac{1}{2}\cos 4x+\frac{3}{8}} \\&=\frac{\cos 8x - 4\cos 4x + 3}{\cos 8x+4\cos 4x+3}

Texas Instruments Resources

In the CK-12 Texas Instruments Trigonometry FlexBook, there are graphing calculator activities designed to supplement the objectives for some of the lessons in this chapter. See http://www.ck12.org/flexr/chapter/9701.

Image Attributions

Files can only be attached to the latest version of None
Please wait...
Please wait...
Image Detail
Sizes: Medium | Original
 

Original text


Help us improve the site! Which of the following best describes your visit today?

I'm a student and I found this site on my own.
I'm a student and my teacher told me to come to this site.
I'm a teacher looking for materials to use in class.
I'm preparing for teacher certification exam, e.g. Praxis II.
Other

Thanks for answering this poll. Your feedback will help us continue to improve the site!